Genetic and phenotypic correlations among reproductive traits of dairy cows. - Ríos-Utrera, Ángel (2010)
The objective of thiswork was to estimate the genetic and phenotypic correlationsamong fertility traits of 317 Holstein Friesian and BrownSwiss cows. Cows were born and reared under subtropicalconditions, during a 20-year period (1986 to 2006), and weredaughters of 116 sires and 199 dams. The study was carriedout in Las Margaritas research station, in Hueytamalco,Puebla, México, which belongs to the Instituto Nacional deInvestigaciones Forestales, Agrícolas y Pecuarias (INIFAP).Fertility traits studied were: days to first service after calving(DFS), calving interval (CI), days open (DO), number ofservices per conception (NSC) and conception rate at firstservice (CR). Genetic correlations were estimated with atwo-trait animal model (bivariate analysis), which includedindividual additive genetic effect as a sole random effect.Main fixed effects were: calving year, calving season andbreed of cow. Analyses were carried out with restrictedmaximum likelihood, using an algorithm free of derivatives.In general, fertility traits were favorably and stronglycorrelated genetically. Estimates of genetic correlations forDFS-CI, DFS-DO, DFS-NSC, CI-DO, CI-NSC, and DONSCwere positive (0,89, 0,89, 0,25, 0,90, 0,59 and 0,97,respectively), while all estimates of genetic correlations thatincluded conception rate to first service (DFS-CR, CI-CR,DO-CR, NSC-CR) were negative (-0,45, -0,62, -0,72, -0,85).The high estimates of genetic correlations between CI andDFS or DO indicate that selection for less DFS or DO wouldreduce CI.